2010
DOI: 10.1631/jzus.b0900391
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic observation and classification criteria of atretic follicles in guinea pigs

Abstract: Abstract:There is a lack of appropriate classification criteria for the determination of atretic follicles in guinea pigs. In the present study, new criteria were established based on the latest morphologic criteria for cell death proposed by the Nomenclature Committee on Cell Death (NCCD) in 2009. Ovaries of guinea pigs were sampled on different stages of estrous cycle, and the morphologic observations of atretic follicles were investigated in serial sections. The results showed that the process of follicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…A normal estrous cycle is divided into four stages: proestrus, estrous, metestrus, and diestrus (Wang et al, 2010). The four stages are obviously affected by estrogen periodicity (Bland, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…A normal estrous cycle is divided into four stages: proestrus, estrous, metestrus, and diestrus (Wang et al, 2010). The four stages are obviously affected by estrogen periodicity (Bland, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was reported in guinea pigs by Rawson et al (1979): the conversion of normal follicles to atretic ones reflected the LH activity of the eCG. Previous works suggested that follicular luteinization and atresia in guinea pigs might be complex and differ from the processes in other mammals (Wang et al, 2010a;2010b). Certainly, the dependence on the selection of antral follicles in guinea pigs warrants further studies, which should allow this system to become a more informative model.…”
Section: Discussionmentioning
confidence: 96%
“…6) were significantly different among the groups (P<0.05) and were in the following sequence: 50 IU group>20 IU group>control group. According to relevant revised classification criteria (Wang et al, 2010b), the follicular atresia and oocyte degeneration in the control group were at the latter Stage III (Fig. 7a) or Stage I (Fig.…”
Section: Effects Of Ecg On Cell Differentiation and Proliferation In mentioning
confidence: 99%
See 1 more Smart Citation
“…The specific protein immunoreactivity was visualized with 0.05% DAB in 10 mM PBS containing 0.01% (V/V) H 2 O 2 for 30 min, and counterstained with hematoxylin. The negative control was normal rabbit serum (NRS) instead of primary antibody, and relative levels of immunostaining were evaluated and repeated at least four times [28][29][30][31]. The images were captured under the microscope.…”
Section: Immunohistochemistrymentioning
confidence: 99%